High-throughput screening of food additives with synergistic effects on high hydrostatic pressure inactivation of budding yeast. Issue 2 (3rd April 2019) - Iguchi, Akinori; Ikarashi, Masaki; Maruyama, Akiko; Hori, Saori (Ujiie); Nomura, Kazuki; Shigematsu, Toru
ABSTRACT: We focused on food additives that enhance the effect of high hydrostatic pressure (HHP) treatment for microbial inactivation. We previously isolated Saccharomyces cerevisiae ultraviolet (UV) mutant strain a1210H12 that does not cause a growth delay under specific high pressure treatment conditions. We conceived that it is possible to screen effective food additives in a high-throughput manner by combining strain a1210H12 with a viable cell count method based on liquid culture, named high-throughput microbial pressure inactivation kinetics analysis system (HT-PIKAS). Here, we analyzed the synergistic effect between food additives and HHP treatment on inactivation of strain a1210H12 using HT-PIKAS. We calculated the inactivation rate in the condition of additive only, HHP treatment only and HHP treatment with additive. As a result, four compounds, benzoic acid, sorbic acid, adipic acid and caproic acid, showed high synergistic effects with HHP treatment and could be selected from more than 30 compounds as safe food additives.